Atributos essenciais da atenção primária à saúde de longevos na percepção de profissionais da estratégia saúde da família - Sulzbach, Cíntia Cristina (2017)
Family Health is a priority strategy for Primary Care in Brazil and aims at health of the aging population. The essential attributes: access, longitudinality, coordination, integrality - characterize a service as a primary care provider. In this sense, our objective is analyze the perception of Family Health professionals about the essential attributes of Primary Care in the care of longevous people, in Palmeira das Missões - RS. This is a qualitative, transversal and exploratory study with 10 professionals, using a semi-structured interview whose questions were based on the Primary Care Assessment Tool. After transcription, thematic content analysis was performed. Categories were categorized according to each essential attribute and subcategories called facilitators and barriers. The project was approved by Research Ethics Committee of the Federal University of Santa Maria, under CAEE nº 61829916.6.0000.5346. The access was characterized by home visits, spontaneous demand, limitation in the temporal access, lack of receptionist and not priority to the long-lived elderly. In longitudinality, there was low professional turnover, record of appointments, team meetings, high demand and recognition of the community agent. Coordination of care was highlighted: electronic medical record, lack of counterreference, decentralized regulation and delayed access to specialized services. The integrality was described by the search for resolution, lack of specific services to the longevous people, predominance of biomedical perspective, diversity of subjects discussed although it does not address about aging. It is concluded that the analysis of the essential attributes in the perception of health professionals is relevant for the qualification of care for the long-lived elderly, a population in greater vulnerability, with the potential to contribute to the development of policies and comprehensive lines of care.